2003
DOI: 10.1142/s0217732303012465
|View full text |Cite
|
Sign up to set email alerts
|

Dilatonic Inflation and Susy Breaking in String-Inspired Supergravity

Abstract: The theory of inflation will be investigated as well as supersymmetry breaking in the context of supergravity, incorporating the target-space duality and the nonperturbative gaugino condensation in the hidden sector. We found an inflationary trajectory of a dilaton field and a condensate field which breaks supersymmetry at once. The model satisfies the slow-roll condition which solves the η-problem. When the particle rolls down along the minimized trajectory of the potential V (S, Y ) at a duality invariant po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 17 publications
5
17
0
Order By: Relevance
“…In the theory of supergravity the Rarita-Schwinger field is associated with the conjectural gravitino, the supersymmetric partner of graviton [33,36,37,38]. In general, the Rarita-Schwinger Lagrangian describes a massive particle with spin− 3 2 [33,38]…”
Section: Rarita-schwinger Fieldmentioning
confidence: 99%
“…In the theory of supergravity the Rarita-Schwinger field is associated with the conjectural gravitino, the supersymmetric partner of graviton [33,36,37,38]. In general, the Rarita-Schwinger Lagrangian describes a massive particle with spin− 3 2 [33,38]…”
Section: Rarita-schwinger Fieldmentioning
confidence: 99%
“…where η is Dedekind's η function, c is a free parameter in the theory and S is a dilaton, T is a moduli and Y is a complex scalar superfield defined by the gaugino condensation U ∼< λ λ >= Y 3 of the E 8 hidden sector [2], and α, β are new parameters that should be determined from observations. The renormalization group parameter b = 15 16π 2 can correspond to the E 8 hidden sector gauge group.…”
mentioning
confidence: 99%
“…A modified string-inspired modular invariant supergravity is proposed here to apply it to inflationary cosmology. Because inflation is concerned with Planck scale physics, the dilaton can be one of the strong candidates for the inflaton [3,4]. We assume that the massless Goldstino is identified with the dilatino S because the mass of S satisfies m SS = 0, where m is defined by m ≡ e K/2 W .…”
mentioning
confidence: 99%
“…Although recently the inflation theories in string theories are extensively and promissingly investigated by various authors [5], here we concentrate on the framework of a supergravity inspired by superstrings, following previous papers [7,8,9]. The well-known difficulty of supergravity is that the potential form gives arise the ηproblem [8], which breaks the slow-roll condition.…”
mentioning
confidence: 99%
“…In this paper, the angular power spectrum in modularinvariant supergravity is investigated in the model where we had shown that the inflation and the supersymmetry breaking occur at once by the interplay between the dilaton field as the inflaton and the condensated gaugesinglet field rolling down the inflationary trajectory, free from the η-problem [9].…”
mentioning
confidence: 99%